ANALYSIS OF FLOOD VULNERABILITY LEVELS IN LANDAK REGENCY USING GEOGRAPHIC INFORMATION SYSTEM - Yance, Yance; Soeryamassoeka, SB; Nurhayati, Nurhayati (Fakultas Teknik Universitas Tanjungpura, 2024)
Law No. 24/2007 defines a disaster as a series of events that threaten and disrupt people's lives caused by natural, non-natural, and human factors, resulting in loss of life, environmental damage, and property loss. Landak Regency is one of the areas in West Kalimantan that is often flooded. Floods in Landak Regency impact people's lives, so they must be minimized. One of the efforts to minimize flooding is by mapping flood vulnerability. Flood vulnerability mapping is one of the early mitigations that utilize technological developments.This article presents the research results that aim to map the level of flood vulnerability in Landak Regency. The mapping was carried out using ArcGIS 10.8 software, and the data used are rainfall data, land use maps, slope, soil type, and land cover.The analysis shows the runoff coefficient rose from 0.16 in 2012 to 0.19 in 2021 due to land use changes converting forests and agriculture to settlements, impacting drainage. Flood vulnerability mapping identified highly vulnerable areas covering 21.41% of Landak Regency, focused near Ngabang, Sebangki, and Mandor, particularly along rivers. Vulnerability in Ngabang District decreased due to upstream spatial control policies, which established it as a protected forest area under regulations. Flood vulnerability assessment against Landak Regency's RTRW revealed flood-prone areas covering 490,097.51 Ha (60.77%), dominated by plantations (303,947.52 Ha), production forests (73,610.58 Ha), and agriculture (47,259.98 Ha). These results highlight the necessity of comprehensive spatial planning to effectively manage flood risks and protect Landak Regency's environment and communities.